2022
DOI: 10.1002/chem.202200335
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics‐Based Approach to Developing Electrocatalytic Variants of Slow Oxidations: Application to Hydride Abstraction‐Initiated Cyclization Reactions

Abstract: Electrochemical oxidant regeneration is challenging in reactions that have a slow redox step because the steady‐state concentration of the reduced oxidant is low, causing difficulties in maintaining sufficient current or preventing potential spikes. This work shows that applying an understanding of the relationship between intermediate cation stability, oxidant strength, overpotential, and concentration on reaction kinetics delivers a method for electrochemical oxoammonium ion regeneration in hydride abstracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The reaction of trisubstituted alkene 5 to yield 6 (Entry 2) was faster than the oxidation of 1, as expected based on the enhanced capability of a trisubstituted alkene to stabilize a cation in comparison to a disubstituted alkene, and the transformation was similarly clean. Notably, this reaction can be conducted on 1 mmol scale to give an 82 % yield and is suitable for electrocatalytic oxidation, [13] showing that these processes can be conducted with substoichiometric quantities of oxidant. The conversion of 7 to 8 (Entry 3) demonstrated that alkene geometry can be conserved in these processes, which is a distinct advantage over the oxidation of vinyl carbamates whereby stereoselectivity for trisubstituted alkene products through hydride abstraction from a methine group in a branched substrate would not be expected.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction of trisubstituted alkene 5 to yield 6 (Entry 2) was faster than the oxidation of 1, as expected based on the enhanced capability of a trisubstituted alkene to stabilize a cation in comparison to a disubstituted alkene, and the transformation was similarly clean. Notably, this reaction can be conducted on 1 mmol scale to give an 82 % yield and is suitable for electrocatalytic oxidation, [13] showing that these processes can be conducted with substoichiometric quantities of oxidant. The conversion of 7 to 8 (Entry 3) demonstrated that alkene geometry can be conserved in these processes, which is a distinct advantage over the oxidation of vinyl carbamates whereby stereoselectivity for trisubstituted alkene products through hydride abstraction from a methine group in a branched substrate would not be expected.…”
Section: Resultsmentioning
confidence: 99%
“…Oxocarbenium ions 162 derived from allylic or benzylic ethers 161 can easily be trapped with nucleophiles other than water without fragmentation (Scheme c). With water as the nucleophile, a hemiacetal is formed, which can fragment to an alcohol and aldehyde (see above) or can be oxidized to an ester. , Other nucleophiles used in the oxoammonium salt-mediated oxidative α-functionalization of benzylic ethers to give products of type 163 are 1,3-dicarbonyl compounds, enols derived from aldehydes, enol acetates, alcohols, and allyl silanes …”
Section: Oxidation Reactionsmentioning
confidence: 99%
“…With water as the nucleophile, a hemiacetal is formed, which can fragment to an alcohol and aldehyde (see above) or can be oxidized to an ester. 1030,1031 Other nucleophiles used in the oxoammonium salt-mediated oxidative α-functionalization of benzylic ethers to give products of type 163 are 1,3-dicarbonyl compounds, 1032 enols derived from aldehydes, 1033 enol acetates, alcohols, 1034 and allyl silanes. 1035 4.7.3.…”
Section: Oxidations Of C Nucleophilesmentioning
confidence: 99%
“…The low concentration of hydroxylamine leads to significant increases in potential when the reaction is conducted under constant current conditions, creating the possibility for substrate and product decomposition through single electron oxidation pathways. These problems were addressed by Lawrence, 180 who showed that constant potential conditions are desirable for these transformations where the potential is substantially higher than the oxidation potential of the hydroxylamine but lower than the oxidation potential of the substrate. Additionally, trifluoroethanol (TFE) is the optimal additive to ensure that the kinetics of oxidant regeneration are suitable for conducting the transformations in a reasonable time frame (Scheme 66).…”
Section: Oxoammonium Ionsmentioning
confidence: 99%